Answer :

Edufirst

Answer:

           [tex]y(x)=\sqrt[3]{sin(x)-3}[/tex]

Explanation:

The differential equation is:

        [tex]\dfrac{dy}{dx}=\dfrac{cos(x)}{y^2}[/tex]

Separate variables:

          [tex]y^2dy=cos(x)dx[/tex]

Integrate both sides:

           [tex]\int y^2dy= \int xcos(x)dx[/tex]

           [tex]\dfrac{y^3}{3}=sen(x)+C[/tex]

          [tex]y^3=3sin(x)+C'[/tex]

Find C' using the inital condtion y(π/2) = 0

          [tex]0=3sin(\pi /2)+C'\\\\0=3+C'\\ \\ C'=-3[/tex]

Then,

          [tex]y^3=3sin(x)-3\\ \\ \\ y=\sqrt[3]{sin(x)-3}\\ \\ \\ y(x)=\sqrt[3]{sin(x)-3}[/tex]

Other Questions